Ageing in place and dementia: A scoping review identifying preconditions and Gerontechnology participation domains - Raymundo, Taiuani Marquine; Lorenzi, Lorena; Huisman, Emelieke; Bet, Patricia; Facioli, Marina Soares Bernardes; Medola, Fausto Orsi [UNESP]; Bernardo, Lilian Dias; Castro, Paula Costa; Kort, Helianthe (International Society for Gerontechnology (ISG), 2024)
Background: Ageing in place(AiP) is a concept whereby older people can continue to live in their own homes as they age despite changes to their health and mobility. The term home does not refer only to living unit itself but goes beyond, such as the community, social network, and other physical spaces that a person occupies and considers as significant. Objective: The aim of the scoping review is to identify ageing in place initiatives that can benefit people with dementia around the world and, specifically in Brazil. Method: A scoping review as well as an expert consultation were executed to give answers to: 1. What are the ageing-in-place initiatives for people with dementia around the world? 2. What are the ageing-in-place initiatives for people with dementia in Brazil? This scoping review followed the methodological framework proposed by Arksey and O’Malley and complemented by Levac, Heather Colquhoun & Kelly K O’Brien. Included articles have to be coming from the last five years (2017-2022), published in Dutch, English, or Portuguese, and addressed the theme of ageing in place and dementia. Furthermore, all types of factors were listed and categorized to factors that appeared in each article and, if necessary, subcategorized what was found in each category. In addition, studies are categorized by applying the Gerontechnology matrix to get an overview of which participation domains are covered regarding ageing-in-place with dementia. Consultation took place online with six experts in gerontology and gerontechnology. Results: A total of 73 articles were eligible. Most publications were published in 2019 and came from Europe and North America. No publications were found in the databases searched in African or Central and South American countries. During the process of categorizing the studies, it was possible to identify Preconditions for ageing in place and these were subdivided into seven subcategories (Health Policies for people with dementia, care policies, ageing in place policies; Usability and acceptance; Age friendly cities and spaces; Research; Development, participatory and co-design; Economy/finance/economic disadvantage/wealth; Education/training program). In addition to the category Preconditions articles could be placed in so called Main Categories. The main categories are organized and aligned with the participation domain in Gerontechnology Matrix. The consultation phase with experts was carried out to help the authors better describe and understand the study categories. Conclusion: Although Ageing in place for dementia has been reported world-wide, it is not offered as such in Brazil. Those articles from other countries described initiatives categorized into preconditions and main categories to realize ageing in place for people with dementia.
Keywords: ageing in place; dementia; gerontechnology